Osteomalacia as a late metabolic complication of Ifosfamide chemotherapy in young adults: illustrative cases and review of the literature. - Church, D; Hassan, A; Harper, S; Wakeley, C; Price, C (2007)
Purpose. Ifosfamide is a drug commonly used in the management of sarcomas and other solid tumours. One potential toxicity of its use is renal tubular damage, which can lead to skeletal abnormalities; rickets in children and osteomalacia in adults. We aimed to characterise this rare complication in adults. Patients. Three illustrative patient cases treated in our institution are presented. All were treated for sarcoma, and received varying doses of ifosfamide during their therapy. Methods. We performed a review of the literature on the renal tubular and skeletal complications of ifosfamide in adults. Papers were identified by searches of PubMed using the terms "osteomalacia," "nephrotoxicity," "Fanconi syndrome," "ifosfamide," and "chemotherapy" for articles published between 1970 and 2006. Additional papers were identified from review of references of relevant articles. Results. There are only four case reports of skeletal toxicity secondary to ifosfamide in adults; the majority of data refer to children. Risk factors for development of renal tubular dysfunction and osteodystrophy include platinum chemotherapy, increasing cumulative ifosfamide dose, and reduced nephron mass. The natural history of ifosfamide-induced renal damage is variable, dysfunction may not become apparent until some months after treatment, and may improve or worsen with time. Discussion. Ifosfamide-induced osteomalacia is seldom described in adults. Clinicians should be vigilant for its development, as timely intervention may minimise complications.